Expectations of Motherhood and Quality of Life. Issue 2 (March 2021) - Adams, Mary K.; Byrn, Mary; Penckofer, Sue; Bryant, Fred; Almonte, Angelica
Abstract: Purpose: The purpose of this study was to examine 1) discrepancies between expectations of motherhood and the experience of motherhood in the first 6 to 12 weeks postpartum, 2) relationships between maternal quality of life, mood, parental attitudes, and expectations, and 3) predictors of quality of life. Study Design and Methods: We used a descriptive, correlational design. The sample consisted of first-time mothers who were at or beyond 34 weeks pregnant with no reported history of anxiety or depression. The following questionnaires were administered during pregnancy and 6 to 12 weeks postpartum: Parenting Expectations Measure, General Anxiety Disorder 7, Edinburgh Postnatal Depression Screen, Intensive Parenting Attitudes Questionnaire, and Ferrans and Powers Quality of Life Index. Results: Sixty-one mothers participated. Based on scores from the Parenting Expectations Measure, 44% of participants had expectations of motherhood that were not met. Expectations were a significant predictor of quality of life during pregnancy and postpartum. Clinical Implications: Unmet expectations are important to understand when identifying modifiable risk factors of postpartum anxiety and depression in women without other risk factors. A discussion of expectations during antepartum care may minimize poor quality of life which is associated with anxiety and depression in women without anxiety and depressive symptoms. Abstract : Expectations of motherhood during pregnancy and the experience of motherhood during the first 6 to 12 weeks postpartum may not always match. In this study of pregnant women and new mothers, almost one-half of new mothers had unmet expectations and these unmet expectations were found to be a significant predictor of quality of life during pregnancy and postpartum.